The Initiator of Women and Their Reasons for Entry in Micro-Enterprises - Jain, Bandana Kumari (Journal of Management, 2021)
This paper aims to describe women and their enterprises and to assess the initiator, and their reasons behind the commencement of their business. The paper deals with the micro-enterprises controlled and managed by a disadvantaged section of women in Biratnagar Metropolitan City. The sample of 54 deprived women running micro-enterprises was selected implying a purposive sampling method. Primary data were collected with a structured questionnaire that was administered by the researcher. The study depicted that there were 3 main motivating factors self-motivation, self-employment attitudes, and educational background of leaning towards micro-enterprises. The disadvantaged section of women due to various social inhibitions and personal reasons, there is a little chance of getting formal jobs in an organized sector. This compelled them to run micro-enterprises. Women belonging to disadvantaged classes are willing for productive involvement in economic gainful activities pushing them to micro-enterprises.